Robot behaviour design, description, analysis and modelling - Nehmzow, Ulrich 1961- (Springer, 2009)
Written to complement and build on Nehmzow's earlier book: Scientific Methods in Mobile Robotics this new book is practical in its approach and includes examples of modelling and analysing observed behaviour based on real-world robotics scenarios. Robots have been changing our lives for some decades now, and will become even more important in the future. The scientific and industrial community have used them extensively in the past to investigate theoretical concepts of cognition, machine intelligence, theories of behavioural mechanisms in living beings, to manipulate and transport objects, or for inspection and exploration tasks. Increasingly, however, robots are also becoming relevant components of political life: industrialised nations are investing large amounts of money into research of care for the elderly, using robots, or for healthcare applications. Entertainment robots occupy a small niche at the moment, but this will increase, and so too will the use of robots in military applications.